2019
DOI: 10.3389/fimmu.2019.01115
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Subserous Vaccination With Helicobacter pylori Vaccine: An Attempt to Establish Tissue-Resident CD4+ Memory T Cells and Induce Prolonged Protection

Abstract: Tissue-resident memory T (Trm) cells are enriched at the sites of previous infection and required for enhanced protective immunity. However, the emergence of Trm cells and their roles in providing protection are unclear in the field of Helicobacter pylori ( H. pylori ) vaccinology. Here, our results suggest that conventional vaccine strategies are unable to establish a measurable antigen (Ag)-specific memory cell pool in stomach; in comparison, gastric subserous in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…Using a new strategy for mucosal vaccination, Stary et al showed that IFN-γ producing CD4 + T RM are pivotal for protection against Chlamydia trachomatis [124,128]. Similar findings have been reported for genital tract herpes simplex virus (HSV) vaccination [120], and gastric subserous vaccination with Helicobacter pylori vaccine [129]. Therefore, identification of mechanisms which promote the generation and retention of CD4 + T RM should be further explored for development of more effective vaccines against a range of human pathogens [130].…”
Section: Cd4 + T Rm Subset Functionmentioning
confidence: 65%
“…Using a new strategy for mucosal vaccination, Stary et al showed that IFN-γ producing CD4 + T RM are pivotal for protection against Chlamydia trachomatis [124,128]. Similar findings have been reported for genital tract herpes simplex virus (HSV) vaccination [120], and gastric subserous vaccination with Helicobacter pylori vaccine [129]. Therefore, identification of mechanisms which promote the generation and retention of CD4 + T RM should be further explored for development of more effective vaccines against a range of human pathogens [130].…”
Section: Cd4 + T Rm Subset Functionmentioning
confidence: 65%
“…But it was less known about CD4 + TRM cells, which might attribute to CD4 + TRM cells, which are less efficiently generated in present mouse models . Fortunately, our previous study demonstrated that CD4 + TRM cells could efficiently generate by vaccination in GSL and protect the stomach from the H pylori infection, but it did not distinguish vaccine‐induced CD4 + TRM cells so that it could not persuasively explore whether the CD4 + TRM cells themselves can induce protective effect …”
Section: Discussionmentioning
confidence: 92%
“…The single‐cell suspension of the stomach was purified with 67%/44% Percoll gradients. After cells were collected, they were washed with 1 mL RPMI 1640 containing 10% FBS …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we used vaccine composed of aluminum adjuvant and CCF (CCF, a recombinant Helicobacter pylori subunit vaccine, a dual-antigen epitope, and a dualadjuvant vaccine constructed as previously described [5]), to vaccinate the gastric subserous layer (GSL) of mice [6]. GSL vaccination-induced mucosal inflammation in the stomach and subsequently a pool of CD4 + tissue-resident T cells (CD4 + T RM ) were established in the epithelium.…”
Section: Introductionmentioning
confidence: 99%